Inculcating the Sense of Modesty (Al-Haya’) in Youth from the Perspectives of the Quran and Sunnah - Rezki Perdani Sawai; Noornajihan Ja‘afar; Sidek Mohd Noah; Steven Eric Krauss (USIM Press, 2024)
Vol. 16 No. 2 (2020): Journal of Maʿālim al-Qurʾān wa al-Sunnah